Anti-Tumor Activity of Orally Administered Gefitinib-Loaded Nanosized Cubosomes against Colon Cancer - Ahmed A. El-Shenawy; Mahmoud M. A. Elsayed; Gamal M. K. Atwa; Mohammed A. S. Abourehab; Mohamed S. Mohamed; Mohammed M. Ghoneim; Reda A. Mahmoud; Shereen A. Sabry; Walid Anwar; Mohamed El-Sherbiny; Yasser A. Hassan; Amany Belal; et al. (MDPI AG, 2023)
Gefitinib (GFT) is a tyrosine kinase inhibitor drug used as a first-line treatment for patients with advanced or metastatic non-small cell lung, colon, and breast cancer. GFT exhibits low solubility and hence low oral bioavailability, which restricts its clinical application. One of the most important trends in overcoming such problems is the use of a vesicular system. Cubosomes are considered one of the most important vesicular systems used to improve solubility and oral bioavailability. In this study, GFT cubosomal nanoparticles (GFT-CNPs) were prepared by the emulsification method. The selected formulation variables were analyzed and optimized by full factorial design and response surface methodology. Drug entrapment efficiency (EE%), transmission electron microscopy, particle size, polydispersity index, in vitro release and its kinetics, and the effect of storage studies were estimated. The chosen GFT-CNPs were subjected to further investigations as gene expression levels of tissue inhibitors of metalloproteinases-1 (TIMP-1) and matrix metalloproteinases-7 (MMP-7), colon biomarkers, and histopathological examination of colon tissues. The prepared GFT-CNPs were semi-cubic in shape, with high EE%, smaller vesicle size, and higher zeta potential values. The in vivo data showed a significant decrease in the serum level of embryonic antigen (CEA), carbohydrate antigen 19-9 (CA 19-9), and gene expression level of TIMP-1 and MMP-7. Histopathological examination showed enhancement in cancer tissue and highly decreased focal infiltration in the lamina propria after treatment with GFT-CNPs.